Editor's note - Sebolai, Kabelo (Journal for Language Teaching, 2023)
We have reached another publication of the Journal for Language Teaching since our move to open access in 2022. Our gratitude goes to all the authors who contributed the articles that this volume comprises. We are even more grateful to all academics who reviewed these articles to help us decide on the quality and fitness of the articles for publication in the journal. We would not have reached this point without your expert input. With a focus on an area of language development that is still a concern for language practitioners at all educational levels, the first five contributions offer research focused on reading development through translanguaging, and a respect for students’ identity, culture, language and ability. In their article, Romylos and Liberty Hove draw on Rosi Braidotti’s (2019) critical research perspective for thinking about teaching and reading for meaning in South African classrooms. Intellectually and pedagogically curious about how their [student] teachers enact and promote teaching strategies reflective of the intersection of pedagogical content knowledge (PCK), English as first additional language (EFAL) and teacher agency, these scholars document that symbiotic relationship to generate insights into teaching and questioning as instances of knowledge production. Among others, Romylos and Liberty Hove conclude by sharing important considerations: that in a complex, multilingual and diverse educational context such as South Africa, diversity, not homogeneity, is the norm (Blommaert & Horner, 2017) and that diversity provides higher education with opportunities rather than constraints in so far as it allows the academy to shift from a ‘difference-as-deficit’ model to a ‘difference-as-resource’ consciousness. Echoing a similar message, Mabena interrogates learners’ reception of translanguaging pedagogy as a strategy for reading English L2 texts, attempting to determine if multilingual speakers in the senior phase reflect the unitary or the differentiated system of translanguaging, or both. Advocating strongly for the need to recognise the inter-related nature of identity, knowledge and language, the author argues against the unfairness of a monolingual system, offering the possibility of embracing students’ linguistic multilingual repertoire as a resource, and not a hinderance. In addition to findings which demonstrate the positive impact of such an approach, Mabena contends that teachers should be capacitated in using translanguaging and its multimodalities in the classroom, for doing so will disrupt the marginalization and alienation of African languages which should be a resource for epistemic access. Focusing on the Intermediate Phase classroom, Ntshangase draws attention firstly, to the reading crisis facing the South African education system, at all levels, and secondly, to the challenges isiZulu teachers face in teaching reading comprehension, especially regarding teaching inclusive reading to at-risk readers in mainstream schools in under-resourced settings. The findings confirm that Intermediate Phase isiZulu teachers struggle to organize meaningful and cohesive reading strategies, that strategies employed are not structured to address specific reading challenges and that consequently, at-risk readers in mainstream schools remain inadequately catered for, thus highlighting the need for more serious interventions, and more consideration for ‘at-risk’ learners. Moving to a focus on the higher education context, Kwarteng, keeping with the overall focus of literacy development and multilingualism, aimed to identify the level of vocabulary that can be acquired by L2 Swahili learners after watching a single Swahili movie with either Swahili or English subtitles. The results showed an increase in the participants’ vocabulary levels after watching the movie, with those in the standard group making statistically significant gains, suggesting that watching a movie in an L2 and visually seeing the subtitles in an L1 has a greater effect on vocabulary acquisition than watching and seeing the subtitles in the L2 only. Once again, this confirms the widely held view that the L1 must and can be exploited profitably for L2 development. Along the lines of the four articles dealt with above, the contribution by Viriri and Ndimande-Hlongwa addresses the challenge faced by student teachers resulting from the assessment of teaching practice in African languages through English as the medium of this assessment. The article highlights the difficulty that this practice poses to the student teachers, regardless of the convenience it offers to the English-speaking assessors involved. By implication, the article highlights issues of validity and fairness in teaching practice assessment. In view of this, the authors conclude: “using English to assess Teaching Practice for African languages compromises the quality of both practice and supervision.” The last two articles focus on issues of language teaching from the point of view of English and Afrikaans. The first by Meyers, seeks to demonstrate that collaboration by student teachers of English as an additional language can either benefit or disadvantage the development of their oral strategic competence and confidence, depending on how their lecturers set this interaction up. Thus, the article recommends that lecturers of these students be aware of this and mindful of how their own interaction with students can either boost or decrease the latter’s growth in oral strategic competence and confidence. The article contributes an important perspective to language development which can easily be overlooked. The last contribution by Vos and Ruiters, raises a concern about the criteria currently used for selecting prescribed poems for Afrikaans Home Language at Grade 12 in South African schools. This concern is that this process is left to the discretion of teachers, who in the authors’ view, might not be adequately equipped to do justice to this important role. The authors recommend that the selection of poems take into account the diversity of Afrikaans, the linguistic background of the learners, and the guidelines from the Basic Education authorities as outlined in the National Curriculum Policy Statement. Ultimately, the concern that these authors raise is one of content validity in the context of a language curriculum. Editor-in-Chief: Dr Kabelo Sebolai Assistant Editor: Dr Avasha Rambiritch December 2023